FACTORS AFFECTING THE TRANSFER OF FUNCTION OF PEOPLE'S RUBBER PLANT TO OIL PALM PLANT IN HARUM SARI VILLAGE TAMIANG HULU DISTRICT ACEH TAMIANG DISTRICT - Fadilah Nurjanah; Riani Riani; Irada Sinta (Jurnal Mahasiswa Agribisnis, 2023)
Crops that are currently in great demand by the community are rubber and oil palm plantation plants. The imbalance of rubber production and the price of rubber sales with maintenance costs for the management of rubber plantations caused farmers to start changing the function of their agricultural land. This research was carried out on the conversion of people's rubber plants in Harum Sari Village, Tamiang Hulu District, Aceh Tamiang Regency in September 2022. This study aims to analyze the influence of the conversion of the people's rubber plant into an oil palm plant in Harum Sari Village, Tamiang Hulu District, Aceh Tamiang Regency. In this study, it used a quantitative method in the form of multiple linear regression analysis using SPSS software version 22. Sampling was carried out using the purvosive method of samples taken in the study as many as 50. The results of this study simultaneously the price of rubber as much as land conversion, farm costs, rubber production, total rubber land area before land conversion, education has a significant effect on the area of rubber land converted. Partially the price of rubber, the cost of farming, rubber production, the total land area and education have a significant effect on land conversion. Keywords: land conversion, rubber farming and oil palm farming.